KAJIAN PEMBENTUK EKSPRESI PADA BANGUNAN MASJID AGUNG KABUPATEN TEGAL - Essa A’la Izzal Afif; Muktiono, Ayub (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2020)
The Great Mosque of Tegal Regency is a mosque located in Tegal Regency. This mosque stands on Ahmad Yani StreetNumber 54 Procot Urban Village, Slawi District. The location of the mosque is in a strategic place, which is on the edge of thesouthern route of Tegal - Purwokerto and facing the Tugu Poci and the GBN Slawi Monument. The current mosque building isthe result of renovations carried out in 2007 to 2010. This mosque can accommodate around 600 worshipers. The mosqueconsists of two floors where the main prayer room is on the second floor. The beauty of this mosque is visible on the dome roofthat blends with the meru roof base. On the four side corners there is also a small dome in the same style as the main dome. Thismosque is the best place of worship for Muslims in Tegal Regency. This mosque is now an icon or characteristic of TegalRegency. The beauty of form is based on the application of aesthetic principles including: unity, balance, rhythm, proportion,scale, sequences, and pressure. The beauty of form can produce the beauty of expression. The beauty of expression is subjectivedepending on the perception of each observer. The beauty of expression can also become an architectural image. The beauty ofexpression can be seen from the elements in the expression, among others: character, color, style / style and material. Overall,the aesthetic value of a building can be achieved through research on the aesthetics of form which includes the beauty of itsshape and expression.